Ignatian Charism: a Vocation for Crossroads - García de Castro Valdés, José (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
Ignatius of Loyola (1491-1556) happened to live during the first part of 16th century, one of the most prolific periods in spiritual movements and theologies, most of them inspired by the Protestant Reform. The rich personality of Ignatius of Loyola, shaped within this framework, led him to seek new proposals of spirituality. In his quest, Ignatius had to choose at crucial crossroads throughout his life. Some of this crossroads are portrayed in this paper: the «new life» with his own «knight past», different theological and spiritual trends, the emergent Humanism and also the Catholic Orthodoxy. The institution inspired by Ignatius’ spiritual experience, the Society of Jesus, has inherited this sense of being present there were the ideologies, cultures or theologies meet, and articulates this implication in her official contemporary documents as «frontiers», «crossroads», «bridges» or «dialogue».
Keywords: Ignatian Charisma; Society of Jesus; General Congregations; Dialogue; Crossroad; Frontiers; Humanism; Ignatius of Loyola; Inquisition